PENGARUH BRAND IMAGE, E-WOM, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM MINDY DI KOTA BATAM - Juniarta Juniarta; Inda Sukati (SCIENTIA JOURNAL, 2026)
This study aims to examine the effect of brand image, Electronic Word of Mouth (e-WoM), and product quality on purchasing decisions of MINDY drinking water in Batam City. This research employs a quantitative approach using a survey method. Primary data were collected through the distribution of questionnaires to 120 respondents who are consumers of MINDY drinking water in Batam City, using a purposive sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26 software. The results indicate that brand image, Electronic Word of Mouth (e-WoM), and product quality have a positive and significant effect on purchasing decisions for MINDY drinking water, both partially and simultaneously. Among the three variables, e-WoM and product quality have a more dominant influence compared to brand image. The coefficient of determination (R²) value of 0.861 indicates that 86.1% of the variation in purchasing decisions can be explained by these three variables, while the remaining portion is influenced by other factors outside the research model. Keywords: Brand Image, E-WOM, Product Quality and Purchasing Decisions